Konsep Key Performance Indicator, Kompensasi Financial, dan Penghargaan: Mendongkrak Kinerja Karyawan - Candra Adi Wijaya; Fathorrahman; Theresia Pradiani (Journal of Trends Economics and Accounting Research, 2023)
This study focuses on analyzing employee performance at BPR Kawan Malang, by considering Key Performance Indicator (KPI), financial compensation, and reward system factors. Employee performance is the result of the effort and energy they put into work. To improve and maintain this performance, productivity assessment is carried out through appropriate indicators, using KPIs. In addition to KPIs, financial compensation and reward systems also have a significant impact on performance. Compensation, as a form of reward, includes a wide range of benefits for employees and the organization. This process of reward distribution has an important role in encouraging good performance. This study aims to analyze the impact of KPIs, financial compensation, and reward systems on employee performance at BPR Kawan. Performance appraisal involves evaluating the extent to which employees meet established standards and communicating that information to employees. Data collection techniques using questionnaires. The method used is a quantitative approach with a sample of 33 employees of BPR Kawan Malang, selected through total sampling. The data analysis technique uses multiple regression analysis. The results showed that KPIs have a significant influence on employee performance, as well as compensation and reward systems with a value of 0.000 sig each; 0,008; 0.000 < 0.05. This conclusion underscores the importance of these elements in stimulating and maintaining superior performance. This research reveals that KPIs, financial compensation, and reward systems play an important role in shaping a work environment that encourages high performance at BPR Kawan Malang.